(untitled) (Applied Biological Research, 2023)
COVID-19 virus of the family Coronaviridae, is an enveloped virus with RNA nucleic acid. The virus spread rapidly from Chinaand was declared a pandemic by the World Health Organization on March 11, 2020. Studies show that some patients who recovered from COVID-19 had a recurrence that arose concern among the scientists. The main purpose of this review is to provide potential hypotheses for the recurrence of COVID-19 infection in both clinical reactivation and reinfection. In reactivation recurrence, hypotheses such as hereditary immunodeficiency, the balance between angiotensin-converting enzyme (ACE) and angiotensin-converting enzyme2 (ACE2), the presence of extracellular exosomes were presented, and in the field of reinfection recurrence, hypotheses such as a false primary RT-PCR test deals with positive, low load of COVID-19 virus, acquired immune system defects and mutations in viral RNA that alter viral epitopes were presented in this review. From the hypotheses presented in this paper, it can be concluded that an imbalance between ACE / AngII / AT1R and ACE2 / Ang1-7 / MasR and the defects in the immune system, can cause defects in the proliferation of NK cells and T lymphocytes,and exosomes contain viral mRNA ultimately leads to reactivation recurrence of the disease. Reinfection recurrence of the COVID-19 may be as a result of the primary false positive report in RT-PCR test, low viral load and inactivation of the immune system, efects in the acquired immune system, and mutations in virus RNA.